Effect of Technology on Elementary Students’ Reasoning & Communication Skills in Science at Lebanese Private Schools: An Exploratory Study - Layal Omar Temsah; Dalal Michel Moukarzel (European Scientific Journal, ESJ, 2018)
With the emergence of multiple technological tools for teaching science such as active boards, mobile devices and tabs, the effectiveness and appropriateness of these tools are yet questionable. Students’ performance in science, especially in the Arab world, is still unsatisfactory as shown by the TIMMS results of 2007 and 2011. In Lebanon, it was interesting to understand what was being done, specifically in elementary schools, to improve students’ outcomes prior to sitting for international exams. The purpose of this study was to explore the perceptions of Heads of private elementary schools, science coordinators, teachers, and students regarding the use of technology, and the extent to which these technologies were enhancing students’ skills. Participants in this study were 164 grade- six students from three private schools in different regions of Beirut, the Lebanese capital. Participants also included three administrators and four teachers of whom three were also coordinators in the corresponding schools. Semi-structured interviews, class observations and questionnaires were used to triangulate the results. Findings revealed that the vision and mission of the school leadership, the teachers’ practices associated with the appropriate integration of technology were key determinants for enhancing students’ perceptions of improvement in reasoning and communication skills in science.